2005
DOI: 10.1002/ijc.20899
|View full text |Cite
|
Sign up to set email alerts
|

Protection of platinum–DNA adduct formation and reversal of cisplatin resistance by anti‐MRP2 hammerhead ribozymes in human cancer cells

Abstract: Resistance to platinum-containing antineoplastic drugs is the major limitation in their clinical use. To elucidate the role of the ABC transporter MRP2 in platinum drug resistance, its expression was analyzed in human cisplatin-resistant cell lines: the ovarian carcinoma line A2780RCIS, the adrenocortical carcinoma line D43/86RCIS and the melanoma line MeWoCIS1. All these cells showed overexpression of MRP2. For reversal of platinum resistance, 2 anti-MRP2 hammerhead ribozymes were introduced into A2780RCIS ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 41 publications
2
52
0
3
Order By: Relevance
“…Of several identified ABC transporters, MRP2 is the principal cisplatin transporter (7)(8)(9). There is a paucity of clinical data regarding any relationship between MRP2 expression and tumor necrosis in patients treated with cisplatin-based neoadjuvant chemotherapy prior to hepatectomy for HCC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of several identified ABC transporters, MRP2 is the principal cisplatin transporter (7)(8)(9). There is a paucity of clinical data regarding any relationship between MRP2 expression and tumor necrosis in patients treated with cisplatin-based neoadjuvant chemotherapy prior to hepatectomy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic toxicity of MRP2 inhibitors at doses necessary for their activity and their poor specificity are the major obstacles in applying them in vivo (8). In attempt to develop alternative, less toxic, and more efficient therapy, Meterna et al specifically inhibited MRP2 protein expression by 2 anti-MRP2 hammerhead ribozymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Reversal of cisplatin resistance by anti-ABCC2 hammerhead ribozymes was demonstrated in human cancer cells. 19 The expression of ABCC2 was specifically reduced by antisense DNA expressed from a CMV expression A 'multitarget multiribozyme' constructed that consisted of three hammerhead motifs directed against transcripts of ABCB1, BCRP and ABCC2 specifically reduced the corresponding transporter ABCB1, BCRP and ABCC2 in all cellular systems. 21 Interestingly, it was shown that bile acid-modified oligodeoxynucleotides are secreted via ABCC2 into bile.…”
Section: Discussionmentioning
confidence: 99%